A neglected opportunity for China's tobacco control? Shift in smoking behavior during and after wives' pregnancy. Issue 1 (December 2016) - Yin, Hao; Chen, Xiao; Zheng, Pinpin; Kegler, Michelle; Shen, Qinfeng; Xu, Biao
Abstract Background Although observational data suggest that men's attempts and behavior at quitting smoking are often stimulated during their spouses' pregnancy, few studies have systematically examined this phenomenon. Methods This was a cross-sectional study which examined Chinese men's smoking behaviors during and after their wives' pregnancy. Women who visited community health centers for routine immunization of their children were approached. Information was mainly collected on men's tobacco use before, during and after pregnancy in July to August 2011. Individual and socio-environmental factors were examined by non-conditional logistical regression analysis to find potential reasons behind men's quitting during pregnancy and maintained this change till the post-partum period. Results Totally 765 of 811 eligible women (94.3%) completed the interview. Prior to pregnancy, 42.9% of husbands smoked; this decreased to 36.34% during pregnancy, a reduction of 6.53%. Although the rate increased to a higher level (43.79%) after delivery, positive changes in men's smoking behavior were detected. One-third (29.88%) reduced the daily number of cigarettes smoked, and nearly half (45.12%) relocated themselves to smoke when their pregnant wives were nearby. Noticeably, those who quit were most likely occasional smokers (Odds Ratio(OR) = 4.83, 95%CI [2.22, 10.48]), smoking less than ten years (OR = 2.80, 95%CI [1.19, 6.58]), not smoking at home (OR = 4.48, 95%CI [1.94, 10.39]), not smoking for social use (OR = 4.05, 95%CI [1.74, 9.41]), under lower financial pressure after the birth of child (OR = 5.28, 95%CI [2.14, 13.02]) and influenced by family members (OR = 2.82, 95%CI [1.25, 6.38]). However, only 22% of spontaneous cessation was maintained postpartum. Most relapses occurred within 6 months after delivery. Conclusions Pregnancy offers an opportunity to decrease smoking amongst Chinese males. Intervention programs involving expectant fathers may be effective to further reduce prevalence of smoking among men in China.